Selection and Monitoring of Assignments in the Audit of Financial Reporting - О. LUBENCHENKO (National Academy of Statistics, Accounting and Audit, 2021)
Problems related to the quality assessment of completed audit assignments are analyzed. As the increasing number of users take management decisions on the basis of audit reports, independent audit is intended to guarantee a sound verification of financial reporting at company level, which can be achieved through the procedures for the assignment quality control.